The Effect of Firm Size, Profitability, and Leverage on Intellectual Capital Disclosure with Audit Committee as Moderator - Septiana, Septiana; Subowo, Subowo (Accounting Analysis Journal, 2020)
The study aims to analyze the effect of firm size, profitability, and leverage on intellectual capital disclosure with audit committee as a moderator. The population in this study are banking companies listed on the Indonesia Stock Exchange in 2014-2016 that is 48 companies. The sample was chosen by purposive sampling method with some criteria so that it was obtained 24 companies with 72 analysis units. The data analysis technique used was moderating regression analysis that processed with SPSS 21. The result of this study showed that firm size has a significant positive effect on intellectual capital disclosure, while profitability and leverage have positive effects but insignificant. The audit committee moderates the influence of firm size on intellectual capital disclosure but the audit committee cannot moderate the influence of profitability and leverage on intellectual capital disclosure. The conclusion of this study is large companies and companies that have high debt levels can minimize business risk by disclosing intellectual capital. Keyword: Audit Committee; Firm Size; Intellectual Capital Disclosure; Leverage; Profitability